If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11(x + -5) = -4 + 2(x + -3) Reorder the terms: -11(-5 + x) = -4 + 2(x + -3) (-5 * -11 + x * -11) = -4 + 2(x + -3) (55 + -11x) = -4 + 2(x + -3) Reorder the terms: 55 + -11x = -4 + 2(-3 + x) 55 + -11x = -4 + (-3 * 2 + x * 2) 55 + -11x = -4 + (-6 + 2x) Combine like terms: -4 + -6 = -10 55 + -11x = -10 + 2x Solving 55 + -11x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 55 + -11x + -2x = -10 + 2x + -2x Combine like terms: -11x + -2x = -13x 55 + -13x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 55 + -13x = -10 + 0 55 + -13x = -10 Add '-55' to each side of the equation. 55 + -55 + -13x = -10 + -55 Combine like terms: 55 + -55 = 0 0 + -13x = -10 + -55 -13x = -10 + -55 Combine like terms: -10 + -55 = -65 -13x = -65 Divide each side by '-13'. x = 5 Simplifying x = 5
| -40x=1640 | | 247=-6x+7 | | (2x-5)-(-5x+7)= | | 3z^2+45=18 | | F(-4)=5x^2-2x+10 | | 5O+Y=16 | | -500x+600=250 | | -12u=-2+8v | | (5x-7)-(4x+2)= | | -7x+-49=-56 | | 1/2(32)(19) | | 45+15+0.75x=40+0.85x | | x^3-x^2+10x+32=0 | | 2x+3(x+5)=4x+18 | | 2x^2-1x=3x^2 | | 17a-2b+3c=126 | | 3r-3=3 | | a-3b+2c=32 | | 4/n=24/18 | | -3u+2v= | | 6a+3b+c=22 | | (x^2-4x-12)/(x^2-x-6) | | .03x+.14=.9x+.08 | | 9.25t+7=20.5t+16 | | 10t-3=t+16 | | 4u=8v | | 6=3+3h | | 5x-7-3x=15 | | N/5=8/10 | | b/3-3b/13=8/13 | | 9t/27t^-5 | | 15/3=45/n |